Long-term optimization of cogeneration systems in a competitive market environment - Thorin, Eva; Brand, Heike; Weber, Christoph (Applied energy, 2005)
A tool for long-term optimization of cogeneration systems is developed that is based on mixed integer linear-programming and Lagrangian relaxation. We use a general approach without heuristics to solve the optimization problem of the unit commitment problem and load dispatch. The possibility to buy and sell electric power at a spot market is considered as well as the possibility to provide secondary reserve. The tool has been tested on a demonstration system based on an existing combined heat-and-power (CHP) system with extraction-condensing steam turbines, gas turbines, boilers for heat production and district-heating networks. The key feature of the model for obtaining solutions within reasonable times is a suitable division of the whole optimization period into overlapping sub-periods. Using Lagrangian relaxation, the tool can be applied to large CHP systems. For the demonstration model, almost optimal solutions were found.